From Agricultural Station to Rural Lab: Sa Granja, an Innovative Center for Agricultural Research, Training, and Cooperation on the Island Of Menorca - Pastrana-Huguet Josep; Casado-Claro Maria-Francisca (European Countryside)
We are at a turning point towards more sustainable socio-economic systems that will shape the future of the agri-food sector by configuring improved production models. This article contends that research, experimentation, vocational training, and cooperation are essential to carry out the transformations needed. To support this contention, this article assesses the evolution of Sa Granja from its creation in Menorca in 1922 until today and its transformation from a General Agricultural Station to a Rural Lab in line with the “living lab” model. It also explores the reasons that made Sa Granja become a benchmark for innovation and training and its contribution to Menorcan agriculture as well as to the transition to a more sustainable agriculture. Finally, some best practices that can be applied elsewhere are highlighted.